(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article examines the development of the educational system in Uzbekistan, especially the organization of educational processes in the higher education system based on the experience of foreign countries. In improving the quality of Education, which is an important factor for the training of highly qualified, competitive and mature personnel who meet the requirements of an international standard in higher educational institutions, the features of the introduction of a credit system in higher education based on the experience of advanced foreign countries were studied.